2016
DOI: 10.1093/ntr/ntw006
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Rats Self-Administer Less Nicotine Than Adults at Low Doses

Abstract: Introduction: Although nearly 90% of current smokers initiated tobacco use during adolescence, little is known about reinforcement by nicotine in adolescents. Researchers are currently investigating whether a potential public health policy setting a tobacco product standard with very low nicotine levels would improve public health, and it is essential to understand whether data generated in adults translates to adolescents, particularly as it relates to the threshold dose of nicotine required to support smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 56 publications
6
21
0
Order By: Relevance
“…Therefore, we believe that the lack of age effects at FR5 are due to the FR schedule being more difficult and that the differences observed at FR1 were not robust and should be interpreted with care. Our findings are consistent with other studies that have shown age differences in responding for low doses of nicotine at differing schedules of reinforcement (Schassburger et al, 2016; Shram et al, 2008). However, in contrast to these other studies, we have found adolescent rats to be more sensitive to the reinforcing effect of low doses of drug at the FR1 schedule.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we believe that the lack of age effects at FR5 are due to the FR schedule being more difficult and that the differences observed at FR1 were not robust and should be interpreted with care. Our findings are consistent with other studies that have shown age differences in responding for low doses of nicotine at differing schedules of reinforcement (Schassburger et al, 2016; Shram et al, 2008). However, in contrast to these other studies, we have found adolescent rats to be more sensitive to the reinforcing effect of low doses of drug at the FR1 schedule.…”
Section: Discussionsupporting
confidence: 93%
“…19,20,50 However, this finding contrasts with other studies showing lower rates of acquisition and nicotine intake under FR schedules and lower breaking points under a PR schedule in adolescents compared to adults. 51-53 This discrepancy may be due to the use of a higher training dose of nicotine and different strain of rat in the present study, as age differences in nicotine self-administration can depend on these factors. 52,53 It is also important to note that adolescent rats were young adults by the end of the PR phase in Experiment 1.…”
Section: Discussionmentioning
confidence: 67%
“…Likewise, numerous laboratories have observed that under a variety of circumstances adolescent rats exhibit greater intravenous (i.v.) self-administration than adults for cocaine (Anker and Carroll, 2010; Wong et al, 2013), amphetamine (Shahbazi et al, 2008), methamphetamine (Anker et al, 2012), and nicotine (Ahsan et al, 2014; Levin et al, 2011; Natividad et al, 2013), although it should be mentioned that some negative findings have emerged (e.g., for cocaine: Harvey et al, 2009; for nicotine: Schassburger et al, 2016; Shram et al, 2008a; 2008b). Critical variables influencing age differences in drug self-administration may include age of initiation during adolescence (with early adolescence perhaps being a particularly sensitive period – Levin et al, 2011), length of access period (Anker et al, 2012), dose and operant schedule (Shram et al, 2008a; and 2008b), dependent measure of focus (e.g., self-administration per se versus drug-seeking behavior – Doherty and Frantz, 2012), and whether animals were group- or isolate-housed (the latter has been reported to increase drug/alcohol abuse vulnerability in adolescent rodents – Butler et al, 2016).…”
Section: Adolescent Sensitivity To Rewardsmentioning
confidence: 99%